Correlation Between Jakarta Cardiovascular Score and Coronary Artery Calcium Score in High-Risk Women at Siloam Hospital Surabaya, Indonesia, 2020-2021. - Imam Mi'raj Suprayoga; Saskia Dyah Handari (Heart Science Journal, 2023)
Background: Coronary Artery Calcium Score (CAC) is an indicator of atherosclerosis and could be used as a reliable noninvasive assessment of coronary artery disease. The Jakarta Cardiovascular Assessment (JAKVAS) is a modified Framingham risk score based on the Indonesian population targeted for developing countries. This study was aimed todetermine the correlation between Jakarta Cardiovascular Score and Coronary Artery Calcium Score in High-Risk Women in Surabaya, Indonesia, in 2020-2021. Method: This study was a retrospective study looking for a correlation between JAKVAS and CAC, with data taken from the medical records of Siloam Hospital Surabaya from 2020-2021. Result: The association between JAKVAS and CAC risk stratification was significant (P < 0.05). Conclusion: Theabsence of CAC is related to a lower risk of cardiovascular events (JAKVAS) than CAC > 0 in high-risk women.